Postoperative pain after endodontic treatment of necrotic teeth with large intentional foraminal enlargement - Ricardo Machado; Daniel Comparin; Sérgio Aparecido Ignácio; Ulisses Xavier da Silva Neto (Restorative Dentistry & Endodontics)
ObjectivesTo evaluate postoperative pain after endodontic treatment of necrotic teeth using large intentional foraminal enlargement (LIFE).Materials and MethodsThe sample included 60 asymptomatic necrotic teeth (with or without chronic apical periodontitis), and a periodontal probing depth of 3 mm, previously accessed and referred to perform endodontic treatment. After previous procedures, the position and approximate size of the apical foramen (AF) were determined by using an apex locator and K flexo-files, respectively. The chemomechanical preparation was performed with Profile 04 files 2 mm beyond the AF to achieve the LIFE, using 2.5 mL of 2.5% NaOCl at each file change. The filling was performed by Tagger's hybrid technique and EndoFill sealer. Phone calls were made to all the patients at 24, 48 and 72 hours after treatment, to classify postoperative pain. Statistical analysis was performed by different tests with a significance level of 5%.ResultsAge, gender, periradicular status and tooth type did not influence postoperative pain (p > 0.05). Only 1 patient (1.66%) reported severe pain after 72 hours. Moderate pain was reported by 7, 4 and 3 patients after 24, 48 and 72 hours, respectively (p = 0.0001). However, paired analyses showed a statistically significant difference only between 24 and 72 hours (p = 0.04). Sealer extrusion did not influence the postoperative pain (p > 0.05).ConclusionsAcute or moderate postoperative pain was uncommon after endodontic treatment of necrotic teeth with LIFE.Trial RegistrationThe Brazilian Clinical Trials Registry Identifier: RBR-3r967t